2015
DOI: 10.1080/11250003.2015.1114157
|View full text |Cite
|
Sign up to set email alerts
|

Diet and first documented data on plastic ingestion ofTrachinotus ovatusL. 1758 (Pisces: Carangidae) from the Strait of Messina (central Mediterranean Sea)

Abstract: The present paper investigates the diet and the food composition of Trachinotus ovatus in the central Mediterranean Sea (Strait of Messina). Moreover, the first documented data on plastic ingestion by T. ovatus are also reported. Samples ranging between 16.5 and 28.0 cm fork length were collected between May and November 2012 in the Strait of Messina (central Mediterranean Sea) by trolling lines. T. ovatus fed mainly on pelagic crustaceans and fishes, although the contribution of mollusks was also important. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 36 publications
(41 reference statements)
4
21
1
Order By: Relevance
“…Interestingly, oceanic juvenile and adult turtles ingested more debris than coastal foragers (Schuyler et al 2013 and literature cited therein). Feeding mode seems to be correlated to the amount of plastic ingested by fish (Anastasopoulou et al 2013;Romeo et al 2015;Battaglia et al 2016). Early life stages of fish are suggested to be increasingly confronted with microplastic, as they dwell close to the ocean surface where floating microplastic concentrate (N. Prinz, unpubl.…”
Section: Microplastic Interactions With Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, oceanic juvenile and adult turtles ingested more debris than coastal foragers (Schuyler et al 2013 and literature cited therein). Feeding mode seems to be correlated to the amount of plastic ingested by fish (Anastasopoulou et al 2013;Romeo et al 2015;Battaglia et al 2016). Early life stages of fish are suggested to be increasingly confronted with microplastic, as they dwell close to the ocean surface where floating microplastic concentrate (N. Prinz, unpubl.…”
Section: Microplastic Interactions With Vertebratesmentioning
confidence: 99%
“…The time a particle spends inside the body (i.e., the retention time) is crucial for estimating chemical exchanges within the body. Many studies investigate the occurrence of plastic within the intestinal tract of an organism without discussing an impact on the animal itself (Boerger et al 2010;Lusher et al 2013;Battaglia et al 2016;Rummel et al 2016;Baalkhuyur et al 2018). Yet, a wealth of studies identify effects of microplastic with artificial concentrations that are far beyond natural levels as currently encountered in the ocean Lusher et al 2017;Critchell and Hoogenboom 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, wild fish showed significantly higher abundance of microplastics than cage-cultured fish (p < 0.05). Microplastic ingestion is closely related to different feeding strategies [22,23,24]. Brandao et al [25] suggested that fouling and high density plastics are examples of items that can be ingested by fish through feeding habitat.…”
Section: Spatial Variationmentioning
confidence: 99%
“…Approximately 150 fish species worldwide have been reported to ingest microplastics [ 30 ], including but not limited to, samples from the Northwest Atlantic [ 31 ], the English Channel [ 19 ], the Mediterranean Sea [ 32 ], Australia [ 29 ], the Adriatic Sea [ 33 ], and China [ 30 ]. The ingestion of microplastics by fish is associated with the abundance of microplastic pollution in the local marine environments and the feeding methods of the fishes [ 32 , 34 ]. Only a limited number of studies have documented microplastic ingestion by fish in Hong Kong, even though the city was determined to be a hotspot of microplastic pollution, with mean microplastic abundance values of 5595 items/m 2 along the shorelines [ 35 ].…”
Section: Introductionmentioning
confidence: 99%